2012
DOI: 10.1093/aje/kwr428
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Violence by Transforming Neighborhoods: A Natural Experiment in Medellin, Colombia

Abstract: Neighborhood-level interventions provide an opportunity to better understand the impact that neighborhoods have on health. In 2004, municipal authorities in Medellín, Colombia, built a public transit system to connect isolated low-income neighborhoods to the city's urban center. Transit-oriented development was accompanied by municipal investment in neighborhood infrastructure. In this study, the authors examined the effects of this exogenous change in the built environment on violence. Neighborhood conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 32 publications
1
83
0
4
Order By: Relevance
“…Cerdá et al (2012) found reduced violence outcomes in some neighborhoods of Medellin, Colombia, that were the focus of an urban development plan that included a transportation system and public space improvements such as additional lighting, new pedestrian bridges and street paths, a library park, and buildings for schools and recreational centers. Vegetation measures and land use diversity indices in those works were derived from remote sensing imagery, and the spatial pattern descriptors were computed from expensive and time-consuming field surveys and appraisals.…”
Section: Introductionmentioning
confidence: 99%
“…Cerdá et al (2012) found reduced violence outcomes in some neighborhoods of Medellin, Colombia, that were the focus of an urban development plan that included a transportation system and public space improvements such as additional lighting, new pedestrian bridges and street paths, a library park, and buildings for schools and recreational centers. Vegetation measures and land use diversity indices in those works were derived from remote sensing imagery, and the spatial pattern descriptors were computed from expensive and time-consuming field surveys and appraisals.…”
Section: Introductionmentioning
confidence: 99%
“…113 However, prior efficacy studies among youth at risk for violence have not led to concurrent work focused on how to prevent firearm injury among the similar populations. Further research is also needed to understand the specific impact of community-level interventions, such as improving neighborhood infrastructure 114 and community-based violence interrupter programs, [115][116][117][118] on firearm assaults and therefore on ED visits. 119 Mass Violence (Table 5) Mass firearm violence is distinct from other forms of firearm injury and death.…”
Section: Suicide (Table 2)mentioning
confidence: 99%
“…This is demonstrated in a study carried out by researchers at the University of Columbia (US), published in the prestigious American Journal of Epidemiology. The article, entitled Reducing Violence by Transforming Neighborhoods: A Natural Experiment in Medellín, Colombia (Cerdá et al, 2012), compares the decline in violence between 2003 and 2008 in neighbourhoods 1 and 2 ("intervention neighbourhoods") compared with other CIT2016 -XII Congreso de Ingeniería del Transporte València, Universitat Politècnica de València, 2016. DOI: http://dx.doi.org/10.4995/CIT2016.2016 .…”
Section: Reduction In Crime In the Neighbourhoods Affected By Metrocablementioning
confidence: 99%